(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the Department of Food Technology, Guru Jambheshwar University of Science and Technology, the current investigation entitled ’Studies on Minimum Processing and Preservation of Fruits and Vegetables through Active Packaging’ was carried out during 2007-2011. The study was carried out in order to prepare minimally processed fruit and vegetable products and prolong their shelf-life through the use of active packaging technology. By following the best unit operations, the measures for the preparation of minimally processed fruits and vegetables (apple, banana, orange, tomato, cauliflower, and spinach) were standardized. Oxygen, carbon dioxide, humidity, ethylene scavengers and chitosan-based film forming solution for coating were optimized for further study treatments under active packaging. Their effects on minimally processed products at RT were observed, while RT and AT reacted well to all commodities. Furthermore, qualitative, bio-chemical, physiological and enzymatic reactions have been observed in both fresh-cut and whole fruits and vegetables. Chitosan coating, followed by ethylene and moisture scavenging treatments, was found to be the most effective.